THE IMPLEMENTATION OF KAMPUS MENGAJAR PERINTIS PROGRAM AS AN ALTERNATIVE SOLUTION TO PROBLEMS IN ELEMENTARY SCHOOLS DURING THE PANDEMIC - Yulianeta, Yulianeta (International Journal of Education, 2023)
The COVID-19 pandemic has led to online learning and stay-at-home measures in Indonesia, enabling internet-based study from home (SFH). The Indonesian government regulates a Study from Home (SFH) policy due to the COVID-19 pandemic. This policy certainly affects the learning process, one of which is the readiness of the learning process in elementary schools. This research aims at revealing and evaluating the implementation of the Kampus Mengajar Perintis (Pioneer Campus Teaching, hereinafter KMP) program as one of Merdeka Belajar Kampus Merdeka programs. This program is conducted by undergraduate students who are spread out across all universities in Indonesia. They are given the chance to teach at elementary schools and are expected to help improve the learning process within three months. This research is conducted using a descriptive Qualitative research method. Students’ responses to the KMP program are collected and used as data. The study involved 17 respondents across schools in West Java. The data is collected through questionnaires, weekly report documents, and students’ final reports through the KMP system. The research shows that the implementation of the KMP program is in accordance with the objectives of the program’s implementation. Students are able to directly participate in helping the learning implementation in Elementary Schools during the COVID-19 pandemic, and they also have applied service-learning in the process. Conclusively, this program serves as a solution for the implementation of blended learning activities in elementary schools and also aids teachers in enhancing the crucial digital literacy required for learning during the pandemic.